Criminal Protection Orders Among Women Victims of Intimate Partner Violence: Women’s Experiences of Court Decisions, Processes, and Their Willingness to Engage With the System in the Future - Holmes, Samantha C. (Journal of interpersonal violence, 2022)
Consistent with a therapeutic jurisprudence framework, court decisions and processes can have a therapeutic or antitherapeutic effect on intimate partner violence (IPV) victims. To maximize therapeutic effects, IPV scholars have advocated for survivor-defined practices that emphasize the importance of engaging with victims in a collaborative manner that promotes autonomy, choice, and control. However, limited research exists in the context of criminal protection orders (POs). The current study addressed this gap by assessing whether criminal PO match (whether victims received the level PO they requested [i.e., PO match] or not [i.e., PO mismatch]) and victims? subjective experiences of the court process were associated with their willingness to use the system in the future to address IPV. In a sample of 187 women whose partners were arrested for IPV, experiencing the court processes as positive (? = .36, p = .001) and court-related fear (? = .41, p < .001) were positively associated with willingness to use the system in the future. Additionally, PO match moderated the association between subjective court experiences and willingness to use the system in the future. Experiencing the court processes as negative (b = .33, p = .005) and validating (b = ?.36, p = .001) was associated with willingness to use the system in the future only for participants who did not receive the PO level they requested. While experiencing the court as positive (b = ?.40, p ≤ .001) was associated with willingness to use the system regardless of PO match, it was most strongly associated for participants who did not receive the PO level they requested. Results suggest the importance of ascertaining strategies to improve victims? experiences with the court, especially when victims? requests are not met, to increase future engagement with the system.